Pengaruh Healthy Lifestyle Dan Brand Ambassador Terhadap Keputusan Pembelian Dengan Niat Beli Sebagai Variabel Mediasi - Putri Mega Utami; RA Nurlinda (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study examines the direct effect of healthy lifestyle and brand ambassadors on purchasing decisions with purchase intention as a mediating variable. Primary data was collected using the survey method by distributing questionnaires to respondents who know NCT Dream as a brand ambassador and have bought and consumed Lemonilo instant noodles. Questionnaires were collected as many as 160 respondents using purposive sampling method. Furthermore, the data is then processed by the method of path analysis, it shows that a healthy lifestyle has an effect on purchase intentions, but brand ambassadors have no effect on purchase intentions. Meanwhile, healthy lifestyle and brand ambassadors influence purchasing decisions. The results also show that a healthy lifestyle influences purchase decisions through purchase intention, but purchase intention does not become a mediating variable between brand ambassadors and purchase decisions. The results of this study are expected to provide input to Lemonilo companies to utilize marketing strategies to increase consumer purchase intentions, as well as offer various promotions that can increase purchasing decisions for Lemonilo instant noodles.